K-12 Voucher Programs and Education Policy - Dan Laitsch (Arizona State University, 2002)
Since the 1983 report, A Nation at Risk, the performance of public schools has been increasingly scrutinized, and a variety of reforms designed to increase student achievement enacted. Among the reforms discussed, much attention has focused on increasing choice and competition in education. While the effectiveness of market oriented reforms have been widely debated, little research has been completed that examines policy maker attitudes toward market reform of education. This study used a researcher designed survey to examine policy maker attitudes toward education and education reform in general, as well as the issue of vouchers more specifically. Findings suggest that policy makers generally accept the market arguments used by voucher supporters, but are also sympathetic to equity concerns and funding issues raised by voucher opponents. Additionally, while more policy makers responding to this survey supported some type of voucher program than opposed vouchers, when viewed in the broader context of reform options, vouchers did not rate highly.